2018
DOI: 10.1016/j.pec.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Do doctors’ attachment styles and emotional intelligence influence patients’ emotional expressions in primary care consultations? An exploratory study using multilevel analysis

Abstract: Understanding how doctors' psychological characteristics influence PPC may help to optimise undergraduate and postgraduate medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Individuals from many sectors charged to help peopleinfected or not from the Covid-19must be able to put themselves in other shoes and see things from their perspective. Studies have shown that doctors' levels of EI and attachment styles have a positive impact on emotional responses of patients [72]. At the present stage doctors' and nursing staffs' EI is a determining factor.…”
Section: 2mentioning
confidence: 97%
See 1 more Smart Citation
“…Individuals from many sectors charged to help peopleinfected or not from the Covid-19must be able to put themselves in other shoes and see things from their perspective. Studies have shown that doctors' levels of EI and attachment styles have a positive impact on emotional responses of patients [72]. At the present stage doctors' and nursing staffs' EI is a determining factor.…”
Section: 2mentioning
confidence: 97%
“…At the present stage doctors' and nursing staffs' EI is a determining factor. Working with doctors and nurses with higher levels of EI make patients feel better, safer, have greater contentment [73] because they feel that professionals also care for their concerns and their needs, beyond the medical part [72,74]. At the same time, emotional intelligence helps the experts to cope better with their work.…”
Section: 2mentioning
confidence: 99%
“…Previous studies that have used this coding system have found that medical visits commonly contain emotional concerns (27)(28)(29). For example, the percentage of general practice visits where patients expressed emotional issues ranged from 54% to 92% (27,(30)(31)(32). Most studies across specialties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the importance of EQ in the medicine and nursing literature (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In medicine, higher EQ has been linked to better patient outcomes, better stress management, and improved wellbeing. Higher levels of EQ in physicians enhances patient outcomes and satisfaction.…”
Section: Emotional Intelligence In the Health Professionsmentioning
confidence: 99%
“…Higher levels of EQ in physicians enhances patient outcomes and satisfaction. 5,22 An assessment of general surgery medical residents reported that EQ scores positively correlated with well-being, and inversely correlated with depression, emotional exhaustion, and depersonalization. 13 In the nursing literature, Rode and colleagues 18 found a relationship between EQ and performance on the National Council Licensure Examination (NCLEX) and the Kaplan Nursing Assessment Test; students with higher EQ performed better on both assessments.…”
Section: Emotional Intelligence In the Health Professionsmentioning
confidence: 99%